Do Prison Visits Have a Spectrum? Visitation Quality and the Varying Impacts for Individuals’ Behavior and Well-Being in Prison - Berghuis, Maria L. (Criminal justice and behavior, 2025)
Scholarship suggests that prison visits can have beneficial as well as potential adverse effects on life in prison. What remains unclear is what explains these heterogeneous effects. In this study, latent profile analysis and regression analyses are used to examine whether the nature of people’s experiences during visits dictates their effects on individuals’ behavior and well-being in prison among more than 2,000 individuals incarcerated in Dutch prisons. The results showed that individuals had diverse, mainly positive experiences during visits which were related to lower incidences of misconduct and higher well-being. However, some visits left individuals feeling stressed, helpless, or guilty, which were related to higher incidences of misconduct (particularly property infractions) and lower overall well-being. These findings suggest that policies aimed at improving visit interactions could have potential beneficial impacts on prison experiences and effects.